PLURALITAS AGAMA MENURUT TOKOH-TOKOH AGAMA DAYAK - Hamid, Abdul (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
Religious plurality is condition that  no rejected by human. One thing that need is haow respond plurality that. So far recorded attitude that used by adherents religion in respond other religions in between exclusivism, inclusivism, and plurality. Exclusivism that  known which claim  absolute truth looked at no corresponding by current condition, thereby also which inclusivism that although no claim ownership absolute but tend see other religions as shadows from one religion, based weakness that owned  by two attitude.  Mode plurality appear  as attitude that looked at  corresponding for respond religious plurality. Like  that there in village Kapul districts Halong regency Balangan. In this village there  various  kind of religion like religion of Islam, Kreisten Katolik, Hindu, Budha, and local religion.This  research aim for known religion pluraly  according to view religion figures Dayak in village Kapul districs Halong regency Balangan. This research is research qualitative by approach sociology  use theory charismatic Max Weber. As for  method this research is methd observation, directly plunge to field in  Village Kapul districs Halong regency Balangan, interview, and documentation.This reaserch concluded that influence charismatic religions figures in Dayak religion when lead  ritual event or in life daily has  give harmonios life for people Dayak in districs Halong regency Balangan.  So religion plurality in this village no  make adherents religion Dayak other religion  as people that intolerance.